New light on the Neolithic of Northern England - Hey, Gill; Frodsham, Paul (Oxbow Books, 2021)
"These papers highlight recent archaeological work in Northern England, in the commercial, academic and community archaeology sectors, which have fundamentally changed our perspective on the Neolithic of the area. Much of this was new work (and much is still not published) and has been overlooked in the national discourse. The papers cover a wide geographical area, from Lancashire north into the Scottish Lowlands, recognising the irrelevance of the England/Scotland Border. They also take a broad chronological sweep, from the Mesolithic/Neolithic transition to the introduction of Beakers into the area. The key themes are: the nature of transition; the need for a much-improved chronological framework; regional variation linked to landscape character; links within northern England and with distant places; the implications of new dating for our understanding of the axe trade; the changing nature of settlement and agriculture; the character of early Neolithic enclosures; and the need to integrate rock art into wider discourse."--